Sheep breeds and production systems in some selected African countries - Galal, E.S.E. (1987)
Describes the major sheep breeds and sheep production systems in Ethiopia and Mauritania. Discussions and data on meat, milk and fresh skin production in relation to the total respective national production; and sheep population in relation to human population and land area included.